Vestibulospinal and Corticospinal Modulation of Lumbosacral Network Excitability in Human Subjects - Sayenko, Dimitry G.; Atkinson, Darryn A.; Mink, Amber M.; Gurley, Katelyn M.; Edgerton, V. Reggie; Harkema, Susan J.; Gerasimenko, Yury P. (Frontiers in Physiology, 2018)
As part of a project aimed to develop a novel, non-invasive techniques for comprehensive assessment of supraspinal-spinal connectivity in humans, the present study sought to explore the convergence of descending vestibulospinal and corticospinal pathways with lumbosacral afferent inputs onto lumbosacral motor pools. Transcutaneous electrical spinal stimulation-evoked motor potentials were recorded from knee and ankle flexors and extensors in resting neurologically intact participants. Descending influences on lumbosacral motor neurons were studied using galvanic vestibular (GVS) or transcranial magnetic stimulation (TMS) to elicit descending vestibulospinal or corticospinal volleys, respectively. Facilitatory conditioning effects of descending corticospinal volleys were manifested by a significant increase of spinally evoked motor potentials in recorded knee and ankle muscles bilaterally, and were observed at the 10 to 30 ms conditioning-test intervals (CTIs); whereas, facilitatory conditioning effects of vestibulospinal volleys manifested at longer latencies (CTIs of 90 and 110 ms, and lasted up to 250 ms). TMS mediated volleys revealed the conditioning effects at both short and long latencies, suggestive of both direct and indirect influence. In contrast, vestibulospinally mediated conditioning effects occurred at longer latencies, consistent with this pathway’s known anatomical and functional interfaces with other descending systems including the reticulospinal pathway and, suggestively, propriospinal interneurons. Our work demonstrates the utility and sensitivity of transcutaneous spinal stimulation in human neurophysiological studies as a technique for quantitative characterization of excitatory conditioning effects in multiple lumbosacral motor pools, obtained through descending pathways. This characterization becomes critical in understanding the neuroplasticity in the central nervous system during motor learning and neurological recovery.